Assesing The Feasibility of Smart Grid Technology on Electrical Distribution Grids - Kanyowa, Tatenda; P. Mahoso, Rindai (EAI Endorsed Transactions on Smart Cities, 2020)
This paper gives a critical analysis framework on the impact of smart grids on electrical distribution grids. It highlights the discrepancies between the developed and developing countries on the adoption of this technology. The concept of smart grids is gaining appreciable recognition in the developed world’s electricity networks. The need to assess the impact of this new technology is critical as the laws of infrastructural clearly show that this is the direction to go if speedy and efficient development is going to be achieved in the developing world. A case study of developing countries was cited as a reference base and compared against developed countries. As developing countries still have the majority of their people still without access to power, the paper shows that the capacity for the implementation of smart grid technologies is ripe for implementation, albeit at a rather high fiscal cost.
Keywords: developing country; developed country; smart grids